Pengaruh Tingkat Pengangguran dan Jumlah Penduduk Terhadap Pertumbuhan Ekonomi di Desa Ringinpitu Kabupaten Tulungagung - Yayang Dewi Arin Maharani; Maria Agatha Sri W H (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effect of the unemployment rate and population on economic growth in Ringinpitu Village, Tulungagung Regency. The high unemployment rate and the increase in population each year are factors that can affect economic conditions in the region. This study uses a quantitative method with multiple linear regression analysis, processed using SPSS software. The results of the study indicate that the unemployment rate has a negative and significant effect on economic growth with a regression coefficient value of -0.283 and a significance value of 0.001 (p <0.05). Meanwhile, the population has a positive and significant effect on economic growth with a regression coefficient of 1.018 and a significance value of 0.000 (p <0.05). The simultaneous test (F test) shows that the unemployment rate and population together have a significant effect on economic growth, with an F-count value of 35.125 and a significance of 0.000 (p <0.05). The Adjusted R² value of 0.621 indicates that 62.1% of the variation in economic growth can be explained by the unemployment rate and population, while 37.9% is influenced by other factors outside this research model. Based on these findings, it is recommended that local governments improve job training programs, create more jobs, and optimize population growth control policies to encourage more stable and sustainable economic growth.